Role of Ultrasound-guided Platelet-rich Plasma in Partial Rotator Cuff Tears: A Prospective Study of 58 Patients - Anshul Dahuja; Rashmeet Kaur; Nabarun Maity; Anjali Handa; Kapil Bansal (Annals of African Medicine, 2026)
Abstract Background: Partial rotator cuff tears (RCTs) are a common cause of shoulder pain and functional limitation, often affecting daily activities and quality of life. Platelet-rich plasma (PRP), owing to its high concentration of growth factors, has emerged as a biological treatment option aimed at enhancing tendon healing and reducing inflammation. Aim: The objective of the study is to evaluate the clinical efficacy of ultrasound-guided PRP injections in partial RCTs. Materials and Methods: A prospective study was conducted on 58 patients with magnetic resonance imaging-confirmed partial RCTs. Patients received two ultrasound-guided PRP injections (5 mL each) at a 3-week interval. Outcomes were assessed using the Visual Analog Scale (VAS) and the university of california-los angeles shoulder score (UCLA shoulder score) at baseline and 6, 12, and 24 weeks. Results: Significant improvement was observed in VAS and UCLA scores at all follow-ups ( P < 0.05). Maximum improvement occurred by 12 weeks and was sustained at 24 weeks. Conclusion: Ultrasound-guided PRP injections are an effective, minimally invasive modality for symptomatic partial RCTs, showing significant pain relief and functional improvement. Further large-scale randomized studies are required to establish its long-term efficacy and optimal treatment protocols.